Implementasi Ds 18b20 pada kolam ikan sistem smart aquaponic - R. Hafid Hardyanto; Prahenusa Wahyu Ciptadi (Jurnal Dinamika Informatika, 2019)
The combination of farming methods with aquaponic systems by collaborating with the application of IoT technology is expected to be able to provide ease in farming. In the aquaponic method, fish that are kept in ponds are in the form of tilapia, where tilapia will live at optimal temperatures ranging from 28 - 32ºC. The survival process of tilapia in aquaponic systems is strongly influenced by temperature, where the temperature can affect the quality of oxygen in water, so that the temperature must be kept at working temperature by designing a controller. This research aims to build, and implement a temperature sensor that can control the aquaponic pool water temperature through a microcontroller that is connected to the user via the internet. The user can monitor the smart aquaponic pool water temperature through the application on the user's android. This research method uses the waterfall development method (MSF), with the Object Oriented Development (OOD) approach. The stages of this research include: problem identification, initial planning, design and design, product testing, and implementation. Data collection methods in this study are: (1). Literature review. (2). Observation (3). Hardware and software testing. Data testing includes hardware testing and software testing. The results of the study are, the system has been able to maintain the temperature of aquaponic pond water developed with IoT technology.